Psychological preparation of freestyle wrestlers during competitions - Lavrentiev, O.; Sergienko, Y.; Antonenko, S.; Krupenya, S.; But, O. (Scientific Journal National Pedagogical Dragomanov University, 2023)
The article examines issues related to the construction of a training process in freestyle wrestling, paying attention to psychological preparation during competitions. Organization and formation of loads, use of technical elements and exercises to improve sports form according to sports qualification and training period.